Archaeological research on the main entrance gate of the medieval settlement Dzhankent in 2019 (Journal of history, 2020)
The article presents some results of integrated archaeological research on the medieval settlementof Dzhankent in 2019. Modern archaeological research the settlement Dzhankent started in the distant1946, when the monument was visited by the head of the Khorezm Archaeological and Ethnographic expeditionS.P. Tolstov with flight intelligence group, which brought together lift the material and produceda visual map of the site. Stationary archaeological research began only in 2005 as part of a tripartiteagreement between the Institute of Ethnology and Anthropology. N.N. Maclay, Russian Academy of Sciences,the Institute of Archaeology. A.H. Margulan MES RK and Kyzylorda state University. Korkyt AtaMES RK. For 15 years of field research, a huge amount of material has been accumulated on the materialculture of the tribes that inhabited the settlement of Dzhankent. However, until now, the defensivestructures and the structure of the main entrance gate of the monument have not been well studied. To fillthe above gap in 2018 was laid excavation number 7 on the Eastern gate of the settlement. During twofield seasons, 200 m2 were excavated at excavation 7 and several construction horizons were revealed.Previously, it can be argued that the main entrance gate of Dzhankent was built by analogy with thenearby cities of southern Khorezm.